A novel role for the fifth component of complement (C5) in cardiac physiology. - Alaka Mullick (PLoS ONE, 2011)
We have previously demonstrated that C5-deficient A/J and recombinant congenic BcA17 mice suffer from cardiac dysfunction when infected with C. albicans blastospores intravenously. During these studies we had observed that, even in the control un-infected state, BcA17 hearts displayed alterations in gene expression that have been associated with pathological cardiac hypertrophy in comparison to parental C5-sufficient C57Bl/6J (B6) mice. Of note was an increase in the expression of Nppb, a member of the fetal gene program and a decrease in the expression of Rgs2, an inhibitor of the hypertrophic response. We now report that C5-deletion has also affected the expression of other elements of the fetal gene program. Moreover deleting the C5a receptor, C5aR, has essentially the same effect as deleting C5, indicating a key role for C5a-C5aR signaling in the phenotype. Having noted a pathological phenotype in the un-infected state, we investigated the role of C5 in the response to cardiac stress. In previous studies, comparison of the expression profiles of C. albicans-infected BcA17 and similarly infected B6 hearts had revealed a paucity of cardioprotective genes in the C5-deficient heart. To determine whether this was also directly linked to C5-deficiency, we tested the expression of 5 such genes in the C. albicans-infected C5aR(-/-) mice. We found again that deletion of C5aR recapitulated the alterations in stress response of BcA17. To determine whether our observations were relevant to other forms of cardiac injury, we tested the effect of C5-deficiency on the response to isoproterenol-induced hypertrophic stimulation. Consistent with our hypothesis, A/J, BcA17 and C5aR(-/-) mice responded with higher levels of Nppa expression than B6 and BALB/c mice. In conclusion, our results suggest that an absence of functional C5a renders the heart in a state of distress, conferring a predisposition to cardiac dysfunction in the face of additional injury.